PERANCANGAN POP-UP BOOK ENSIKLOPEDIA HEWAN LAUT LANGKA UNTUK ANAK-ANAK - ZAKHIA AMINI Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to introduce rare sea animals to children through the encyclopedia pop-up media for rare marine animals in order to motivate children to read and study sea animals that will be invited to work in a fun and unusable way. The method used in this design is the glass box method. Data analysis methods on the 5W + 1H technique are (what, where, who, why, when and how) to make it easy to find solutions to the problems at hand. This pop-up about endangere  marine animals is given the title "Endangered Marine Animal Encyclopedia". This book is designed using visual communication design theory, child psychology, media, books, pop-up books, illustrations, colors, layout, and typography. The design of a rare sea animal encyclopedia pop-up book as the main media and this design has supporting media such as posters, xbanners, stickers, notebooks, tumblers, lunch boxes, and t-shirts.Keywords: Pop-up book, encyclopedia, endangered sea animals